Mechanical homogeneous continuous dynamical systems holor algebra-steady-state alternating velocity analysis - Fijałkowski, Bogdan (Zielona Góra: Uniwersytet Zielonogórski)
In this article, a new mathematical representation of the sinusoidal alternating velocity, force and power by means of some complex quantities, termed "holors" is proposed. The word holor is a term to describe a mathematical entity that is made up of one or more independent quantities, and includes complex numbers, scalars, vectors, matrices, tensors and other hypernumbers. Holors, thus defined, have been known for centuries but each has been developed more or less independently, accompanied by separate nomenclature and theory.
Keywords: force; velocity; power; holor